The importance of early diagnosis of Chagas disease congenital (Research, Society and Development, 2022)
Introduction: Chagas disease (CD) or American trypanosomiasis is a neglected and multisystemic anthropozoonosis that can affect the cardiovascular, digestive, and central nervous systems. The congenital transmission of Trypanosoma cruzi is considered one of the main sources of infection of the disease worldwide, this type of infection happens vertically, that is, during pregnancy. The objective of this work is to highlight the importance of early diagnosis of Congenital Chagas disease. Methodology: This is systematic bibliographic research, of a descriptive nature, with a qualitative approach. For the construction of the study, the following databases were used: Scientific Electronic Library Online – SciELO, U.S Library of Medicine – PubMed, and the Virtual Health Library (BVS). Results: The results obtained present the main methods of laboratory diagnosis of congenital Chagas disease, highlighting the high number of women of childbearing age infected by T. cruzi, enabling vertical transmission and its complications. Conclusion: The need to create new strategies to optimize the control and prevention of congenital Chagas disease, in addition to the development of new screening protocols.